The Influence of the Problem-based Learning (PBL) Model on the Creativity and Problem-Solving Skills of Elementary School Students - Fa'iqoh, Endah Elok; Waris; Rina Sugiarti Dwi Gita (Universitas Pendidikan Ganesha, 2025)
The low level of creativity and problem-solving skills among elementary school students remains a persistent challenge in education, often caused by teacher-centered approaches that limit opportunities for learners to explore and express innovative ideas. This condition highlights the urgency of designing learning models that actively engage students in constructing knowledge while fostering higher-order thinking. This study aimed to examine the effectiveness of the Problem-Based Learning (PBL) model in enhancing students’ creativity and problem-solving skills. The research applied a quasi-experimental method with a pretest-posttest only control group design, involving 60 sixth-grade students divided into experimental and control groups. Data were collected using creativity and problem-solving tests, which were developed and validated according to standardized procedures. The data analysis employed an independent sample t-test to compare learning outcomes between groups. The findings reveal that students in the experimental group demonstrated significantly higher levels of creativity and problem-solving skills compared to those in the control group. Conceptually, these results indicate that the PBL model encourages students to generate original ideas, analyze complex situations, and construct critical solutions collaboratively. The study concludes that PBL is an effective pedagogical strategy to promote creativity and problem-solving as essential 21st-century competencies, with implications for strengthening innovative practices in elementary education.